ϵ-Henig Saddle Points and Duality of Set-Valued Optimization Problems in Real Linear Spaces - Zhi-Ang Zhou (The Scientific World Journal)
We study ϵ-Henig saddle points and duality of set-valued optimization problems in the setting of real linear spaces. Firstly, an equivalent characterization of ϵ-Henig saddle point of the Lagrangian set-valued map is obtained. Secondly, under the assumption of the generalized cone subconvexlikeness of set-valued maps, the relationship between the ϵ-Henig saddle point of the Lagrangian set-valued map and the ϵ-Henig properly efficient element of the set-valued optimization problem is presented. Finally, some duality theorems are given.